Morphological changes in the lower estuarine coastal sector and socio-environmental impacts – Amapá: between 1992 and 2022 - Baia, Maxwell Moreira; Junior, Orleno Marques da Silva (Revista Brasileira de Geomorfologia, 2025)
Coastal regions are transitional areas between terrestrial and marine environments, with dynamic ecosystems, high biodiversity, economic productivity, population density and environmental fragility. The Amapá Coastal Zone is 800 km long and is influenced by atmospheric and oceanographic agents as well as the Amazon River. The study examined the variation between erosion and accretionary processes and their consequences, such as loss of infrastructure, lack of energy and increased saline intrusion in communities between the Gurijuba and Araguari rivers, including the Bailique archipelago. The physiographic characteristics, fieldwork and a multi-temporal series between the years 1992, 2005, 2014 and 2022 were analyzed. It was identified that 60% of the area presents accretion processes, represented by the formation of muddy banks, tidal flats and the clogging of the mouth of the Araguari River, while 40% suffers erosion, affecting 14 of the 20 monitored communities, highlighting the opening of drainages and modification of hydrodynamics. The deficiency in the management of these modifications has generated isolated and ineffective mitigating actions, aggravating the effects of erosion and wasting resources. If current trends are maintained, including forecasts of increased extreme weather events and sea level, more losses will occur, causing irreversible changes in local morphology and hydrodynamics in the short term.